A systematic review of research on attitudes towards and willingness to engage in consensual non-monogamy among emerging adults: methodological issues considered. Issue 1 (3rd April 2017) - Sizemore, Kayla M.; Olmstead, Spencer B.
ABSTRACT: Research on consensual non-monogamy (CNM) has received increasing attention over the last decade. Scholars have noted that research on CNM behaviour has encountered important methodological challenges. Attitudes towards CNM and willingness to engage in CNM are two components that have received comparatively less attention. Whereas others have reviewed the methodological limitations of research on CNM behaviour, a critical examination of the methodological trends in research on CNM attitudes and willingness to engage in CNM has yet to be conducted. We systematically reviewed and critique the methodology used in CNM research between 1974 and 2017. Specifically, we examined research on attitudes towards and willingness to engage in CNM during the developmental period of emerging adulthood. Several methodological trends were found across 23 empirical articles, including sample characteristics, recruitment and sampling strategy, measurement, and overall methodology and focus. Despite general commentary among researchers in this field, this review concludes that CNM research has shown little improvement with regard to addressing limitations in methodological approaches since the 1970s. We conclude with discussion of future research that includes study replication, sampling, and measurement.